1992
DOI: 10.1080/09553009214550641
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Ligands as Radioprotectors: Molecular Studies with Hoechst 33342 and Hoechst 33258

Abstract: Following earlier reports of radioprotection of cells by Hoechst 33342, we have investigated radioprotection of isolated DNA by the minor groove binders Hoechst 33258 and Hoechst 33342. Analysis of radiation-induced single strand breakage in plasmid DNA (pBR322) showed concentration-dependant protection, up to a dose-modifying factor of 9.3 for 25 microM Hoechst 33258, at which the ligand: bp ratio was 0.67. Since the ligands bind at discrete sites along DNA, sequencing gel analysis was used to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…X-ray crystallography (3, 4) studies of complexes with synthetic oligonucleotides confirmed early evidence from DNA binding studies that the ligands are minor groove binders with strong AT selectivity (5). The unexpected radioprotective activity of Hoechst 33342 in cultured cells was first reported in 1984 (6), subsequently confirmed (7,8), and extended with the demonstration of in vivo radioprotection of mouse lung after i.v. administration (9).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…X-ray crystallography (3, 4) studies of complexes with synthetic oligonucleotides confirmed early evidence from DNA binding studies that the ligands are minor groove binders with strong AT selectivity (5). The unexpected radioprotective activity of Hoechst 33342 in cultured cells was first reported in 1984 (6), subsequently confirmed (7,8), and extended with the demonstration of in vivo radioprotection of mouse lung after i.v. administration (9).…”
Section: Introductionsupporting
confidence: 59%
“…The bibenzimidazole ligands (exemplified by Hoechst 33258) have been shown by affinity cleavage (12), foot printing (13) and X-ray crystallographic studies (8) to bind at discrete sites in the minor groove characterized by 3-4 consecutive AT bp. Equilibrium binding studies have established that the dissociation constants (K d ) for the high affinity sites generally range from 1-100 nM, depending on conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is often used as a chromosomal stain [3] [4]. Numerous studies have been reported on its interactions with DNA, the effects of this binding on transcription and translation [5], and on the inhibition of radiation-induced strand breakage [6] employing an array of analytical methods, e.g., optical spectroscopy [2 ± 9], footprinting studies [10 ± 13], kinetics studies of the DNA-binding process [8] [9], X-ray-diffraction studies on single crystals [14 ± 20], and 1 H-NMR spectroscopy [21 ± 29]. These studies have shown that Hoechst 33258 binds to the minor groove of DNA, covering about four AT-base pairs and forming intermolecular H-bonds between thymidine-O-atoms and the imino H-atoms of both benzimidazole moieties.…”
Section: Protonation Equilibria Of Hoechst 33258 In Aqueous Solutionmentioning
confidence: 99%
“…They may be used as radioprotector [1], antimicrobial [2,3], antitumor [4 6] agents, etc. If such a nucleotide binding compound besides high specificity and affinity to substrate also has properties convenient for monitoring (e.g.…”
mentioning
confidence: 99%